DEKONSTRUKSI SOSIAL MELALUI FOTO HOAX - Afusa Nidya Kinasih (Institut Seni Indonesia Yogyakarta, 2019)
Social Deconstruction Through Hoax Photo. The Governor of DKI Jakarta, Basuki Tjahaya Purnama was sentenced to 2 years in prison due to a blasphemy case that occurred in 2016 ago. As a result of this incident, the FPI mass organization (Front Pembela Islam) held an action